2021
DOI: 10.1136/bmjopen-2020-044525
|View full text |Cite
|
Sign up to set email alerts
|

Associations between daily screen time and sleep in a racially and socioeconomically diverse sample of US infants: a prospective cohort study

Abstract: ObjectiveTo determine the associations between screen media use and sleep throughout infancy (3–12 months).DesignProspective Nurture birth cohort.SettingNorth Carolina, USA, 2013–2015.ParticipantsWomen enrolled in their second to third trimester, completed a phone interview after birth, and completed home visits at 3, 6, 9 and 12 months post partum.Primary and secondary outcome measuresWomen reported the usual hours their infants slept during the day and night and their infants’ usual use of five screen media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Our findings are also consistent with studies that found household and demographic characteristics such as educational attainment, race and ethnicity, child age and HFI influence sleep duration for older children 42,43 with limited literature on children under the age of 5. Additionally, behavioral characteristics such as higher amounts of screen time [44][45][46] and SSB intake 27,47 being associated with inadequate sleep are also consistent with findings reported previously in the literature. Sleep is perceived to be one of many potential mediators for the effects of low socioeconomic status and physical and mental health.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are also consistent with studies that found household and demographic characteristics such as educational attainment, race and ethnicity, child age and HFI influence sleep duration for older children 42,43 with limited literature on children under the age of 5. Additionally, behavioral characteristics such as higher amounts of screen time [44][45][46] and SSB intake 27,47 being associated with inadequate sleep are also consistent with findings reported previously in the literature. Sleep is perceived to be one of many potential mediators for the effects of low socioeconomic status and physical and mental health.…”
Section: Discussionsupporting
confidence: 89%
“…This is particularly notable given the American Academy of Pediatrics recommends avoiding all media use in children younger than 18 months (with the exception of video chatting) [ 31 ]. Other studies have found similar high rates of TV exposure among one-year-old infants [ 32 ]. Improved counseling and interventions to limit screen time are needed.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, more screen time was related to a shorter longest sleep episode but a longer daytime sleep for toddlers. Few studies examined the relationships between screen viewing and daytime sleep and longest sleep episode ( 35 ). In China, children always do not attend kindergarten until three years old.…”
Section: Discussionmentioning
confidence: 99%